Inspectorate Supervision of the Accountability of Village Fund Management in Panca Rijang District - Fenny Adila; Nurjannah Nonci; Muliani Samiri; Abdul Jabbar (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to find out and analyze the influence of Inspectorate supervision on the accountability of Village Fund management in Panca Rijang District, Sidenreng Rappang Regency. Inspectorate supervision is an important aspect in realizing transparent, effective, and accountable village governance, especially in the management of Village Funds which have a fairly high risk of irregularities. This study uses a quantitative approach with data collection techniques through observation, literature review, and distribution of questionnaires to Inspectorate and village officials. The number of respondents in this study was 106 people. Data were analyzed using the SPSS application through validity, reliability, normality, and simple linear regression analysis. The results of the study show that the supervision of the Inspectorate has a positive and significant effect on the accountability of the management of Village Funds in Panca Rijang District. This is evidenced by the value of the correlation coefficient (R) of 0.938 which shows a very strong relationship, and the value of the determination coefficient (R Square) of 0.880 which means that the supervision of the Inspectorate has an influence of 88% on the accountability of the management of the Village Fund, while the rest is influenced by other factors outside the research. In addition, the results of the hypothesis test showed a significance value of less than 0.05 so that the research hypothesis was accepted. These findings show that the better the supervision carried out by the Inspectorate, the higher the level of transparency, accountability, regulatory compliance, effectiveness of the use of funds, and the quality of reporting on the management of Village Funds.